Modelling Water Flow in Unsaturated Porous Media Accounting for Nonlinear Permeability and Material Heterogeneity - Szymkiewicz, Adam.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
The book focuses on two issues related to mathematical and numerical modelling of flow in unsaturated porous media. In the first part numerical solution of the governing equations is discussed, with particular emphasis on the spatial discretization of highly nonlinear permeability coefficient. The second part deals with large scale flow in heterogeneous porous media of binary structure. Upscaled models are developed and it is shown that the presence of material heterogeneities may give rise to additional non-equilibrium terms in the governing equations or to hysteresis in the averaged constitutive relationships.
Introduction -- Mathematical Models of Flow in Porous Media -- Numerical Solution of Flow Equations -- Computation of Inter-Nodal Permeabilities for Richards Equation -- Upscaling from Darcy Scale to Field Scale -- Flow in Binary Media with Heterogenous Hydraulic Diffusivity -- Flow in Binary Media with Heterogenous Air-Entry Pressure.
Keywords: Earth sciences; Hydrology; Geophysics; Hydrogeology; Earth Sciences; Hydrogeology; Hydrology/Water Resources; Geophysics/Geodesy.; Electronic books